Cervical Pessary Plus Progesterone for Twin Pregnancy with Short Cervix Compared to Unselected and Non-Treated Twin Pregnancy: A Historical Equivalence Cohort Study (EPM Twin Pessary Study) - Marcelo Santucci França; Alan Roberto Hatanaka; Valter Lacerda de Andrade Junior; Julio Elito Junior; David Baptista Silva Pares; Tatiana Emy Nishimoto Kawanami Hamamoto; Stephanno Gomes Pereira Sarmento; Rosiane Mattar; Antonio Fernandes Moron (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The present study aims to determine if the use of cervical pessary plus progesterone in short-cervix (≤ 25 mm) dichorionic-diamniotic (DC-DA) twin pregnancies is equivalent to the rate of preterm births (PBs) with no intervention in unselected DC-DA twin pregnancies. Methods A historical cohort study was performed between 2010 and 2018, including a total of 57 pregnant women with DC-DA twin pregnancies. The women admitted from 2010 to 2012 (n = 32) received no treatment, and were not selected by cervical length (Non-Treated group, NTG), whereas those admitted from 2013 to 2018 (n = 25), were routinely submitted to cervical pessary plus progesterone after the diagnosis of short cervix from the 18th to the 27th weeks of gestation (Pessary-Progesterone group, PPG). The primary outcome analyzed was the rate of PBs before 34 weeks. Results There were no statistical differences between the NTG and the PPG regarding PB < 34 weeks (18.8%; versus 40.0%; respectively; p = 0.07) and the mean birthweight of the smallest twin (2,037 ± 425 g versus 2,195 ± 665 g; p = 0.327). The Kaplan-Meyer Survival analysis was performed, and there were no differences between the groups before 31.5 weeks. Logistic regression showed that a previous PB (< 37 weeks) presented an odds ratio (OR) of 15.951 (95%; confidence interval [95%;CI]: 1.294-196.557; p = 0.031*) for PB < 34 weeks in the PPG. Conclusion In DC-DA twin pregnancies with a short cervix, (which means a higher risk of PB), the treatment with cervical pessary plus progesterone could be considered equivalent in several aspects related to PB in the NTG, despite the big difference between these groups.